Pyomyositis is not only a tropical pathology: a case series. (December 2016) - Comegna, Laura; Guidone, Paola; Prezioso, Giovanni; Franchini, Simone; Petrosino, Marianna; Di Filippo, Paola; Chiarelli, Francesco; Mohn, Angelika; Rossi, Nadia
Abstract Background Pyomyositis is an acute bacterial infection of skeletal muscle that results in localized abscess formation. This infection was thought to be endemic to tropical countries, and is also known as "tropical pyomyositis". However, pyomyositis is increasingly recognized in temperate climates and is frequently associated with an immunosuppressive condition, such as human immunodeficiency virus, malignancy, and diabetes mellitus. It is also found in healthy and athletic people after strenuous or vigorous exercise or following localized and possibly unnoticed trauma. It can be primary or secondary to neighboring or remote infection. Primary pyomyositis is a rare condition that can affect children and adolescents. Diagnosis can be delayed because the affected muscle is deeply situated and local signs are not apparent. This delay in diagnosis can result in increased morbidity and a significant mortality rate. The pediatric population, which comprises 35% of the reported pyomyositis cases, is an especially difficult subset of patients to diagnose. Case presentation In our series, we describe the cases of four previously healthy Caucasian children who were admitted to our Pediatric Department with different clinical presentations. Pyomyositis in our patients was related to factors affecting the muscle itself, including strenuous exercise and direct muscle trauma. Therapy was started with a cephalosporin antibiotic and teicoplanin was subsequently added. The minimum length of therapy was 3 weeks. Conclusions The diagnosis of pyomyositis in our patients, none of whom were immune-compromised, is confirmation that this disease is not an exclusive pathology of tropical countries and demonstrates that there is an increasing prevalence of pyomyositis in temperate climates.